Healthy eating promotion at the workplace: the European programme FOOD (Fighting Obesity through Offer and Demand) - Leaute, Romane (Revista Española de Nutrición Humana y Dietética, 2019)
VIII Congreso Iberoamericano de Nutrición. ¿Nutrición basada en la videncia o en la evidencia?